PENGARUH GAYA MENGAJAR GURU DAN PEMBERIAN REWARD-PUNISHMENT TERHADAP MINAT BELAJAR SISWA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS V SEKOLAH DASAR - Astuti, Vitri; Siti Nurjanah; Pina Indah Sayekti; Nining Setyaningsih; Sumardi, Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the influence of teaching styles and the provision of rewards and punishments on students' interest in learning Civics in the fifth grade of MI Muhammadiyah Karanganyar. This is a quantitative study. The researcher uses a quantitative approach with regression. The data analysis technique employs statistical formulas, namely simple linear regression and multiple regression. The sampling technique used in this study is saturated sampling. The data collection techniques include questionnaires and documentation. The results of the analysis conclude that teaching styles and the provision of rewards and punishments significantly positively influence students' interest in learning Civics in the fifth grade of MI Muhammadiyah Karanganyar. Teaching styles have a greater influence compared to rewards and punishments, but both significantly contribute to increasing students' interest in learning. The regression model used in this study is quite strong in explaining the variation in students' interest in learning, with 64% of the variation explained by teaching styles and the provision of rewards and punishments.